APLIKASI SISTEM PEMBELAJARAN JARAK JAUH (E-LEARNING) BERBASIS EDMOODO UNTUK MENDUKUNG PENGEMBANGAN PENDIDIKAN TINGGI KEAGAMAAN ISLAM - Sunhaji; Yuli Ani Setyo Dewi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2020)
The government has arranged distance education based on Law Number 20 of 2003 concerning the National Education System (SISDIKNAS), which is meant by distance education is education where students are separated from educators and learning uses various learning resources through technology, common problems in education in Indonesia, which is an inadequate learning system, seen from the learning methods, learning media, and materials that are still not appropriate in their use. This causes the low student learning outcomes, which are influenced by various learning methods that are less precise. This research will be conducted on student achievement in the eyes of Multicultural Education at STITNU AL-Hikmah Mojokerto using edmoodo-based think pair share methods and conventional systems, based on Independent Sample T-Test analysis, obtained Sig. (2-tailed) of 0.879> 0.05, then according to the basis of decision making in the independent Sample T-Test, it can be concluded that Ho is accepted and Ha is rejected, which means that there is no difference between the average learning achievement of the experimental group and the control group